THE ROLE OF PSYCHOLINGUISTICS IN EDUCATION - M. Abduganiyeva; Sh.Obidova; Sh. Turg’unova (Recent scientific discoveries and methodological research, 2025)
This article explores the role and significance of psycholinguistics in the education system. By analyzing the effectiveness of a psycholinguistic approach to language learning and usage, it highlights its contribution to improving the learning process. The article discusses the importance of applying psycholinguistic principles when considering individual differences among learners, selecting teaching methods, and developing learning materials. It also proposes ways to enhance students' language skills, communication abilities, and motivation to learn based on psycholinguistic knowledge. In conclusion, the article emphasizes the role of psycholinguistics in modern education systems and its importance in improving the quality of the learning process.